Chirality Evolution of Supramolecular Helices by Electron Transfer Assisted Secondary Nucleation - Laiben Gao; Xiaoqiu Dou; Chao Xing; Kaikai Yang; Changli Zhao; Chuanliang Feng (Advanced Science)
Abstract Chirality evolution is ubiquitous and important in nature, but achieving it in artificial systems is still challenging. Herein, the chirality evolution of supramolecular helices based on l‐phenylalanine derivative (LPF) and naphthylamide derivate (NDIAPY) is achieved by the strategy of electron transfer (ET) assisted secondary nucleation. ET from LPF to NDIAPY can be triggered by 5 s UV irradiation on left‐handed LPF‐NDIAPY co‐assemblies, leading to NDIAPY radical anions and partial disassembly of the helices. Meanwhile, spontaneous reversion of radical anions into monomers occurs upon removal of UV light, and the surface of residual co‐assemblies can accelerate the reversion process. This surface accelerated reversion of ET further facilitates the secondary nucleation‐elongation events, giving rise to the formation of scale‐amplified and g vale‐increased left‐handed helices. Meanwhile, chirality evolution controlled by ET assisted secondary nucleation process can be also realized by adding the prepared LPF‐NDIAPY co‐assemblies into the total ET system. This study may provide a useful approach to constructing and modulating diverse chiral structures by manipulating the secondary nucleation process.